The Influence of Circulation Patterns on The Visitor Distribution in A Shopping Mall Case Study Palembang Icon Shopping Center, Palembang City - Jessica Oktaviana; Dhita Wahyu Anggraeni (Journal of Artificial Intelligence in Architecture, 2022)
Physiological needs are the most basic human needs. Shopping is one of the measures to fulfill physiological needs, such as clothing, foods, and drinks. Most people prefer to shop in shopping centers as it is more convenient and secure due to its regular spatial pattern, forming a good circulation pattern for their visitors. Palembang Icon is a shopping center in Palembang, located on Jl. POM IX, Lorok Pakjo, Ilir Barat I District, Palembang City, South Sumatra which considered has a good circulation pattern. Palembang Icon has a mall circulation pattern, namely a linear circulation pattern, one lane intended so that all retailers get a strategic place and the circulation orientation becomes clear. This research discusses the Palembang Icon shopping center's circulation pattern and analyzes its influence on the distribution of visitors by using the space syntax method with simulation using the DepthMapX application. The result shows that the circulation space's shape is closed, and the configuration of the circulation path is entirely a linear circulation pattern.